A Program Package for Automated Serials Control - Lalitha, M. R.; Ravichandra Rao, I. K. (Journal of Information and Knowledge, 2014)
Describes a modular, automated serials control system that has been developed using dBase III plus software. The input, processing and output for each module and file requirements for the system are highlighted.